2020
DOI: 10.15560/16.2.253
|View full text |Cite
|
Sign up to set email alerts
|

New records of Myxomycetes from Peru

Abstract: We report 19 species of Myxomycetes for first time in Peru. Macbrideola spinispora L.M. Walker, G. Moreno & S.L. Stephenson, previously known only from the type collection from Costa Rica, is now reported for South America, enlarging its distribution considerably. The Myxomycetes were collected in Wayqecha Biological Station, a conservation area in the Cuzco region. The specimens were deposited in the South Peruvian Herbarium (HSP) and the Real Jardín Bot&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…Among the species identified in the present study, A. cinerea, P. cinereum, P. viride and S. fusca are common in ground litter and other microhabitats (Bezerra et al 2014). Some of the species obtained in this study are typically found in the ground litter, such as C. leucocephalum and L. scintillans, which have records as foliicolous in Atlantic Rainforest and Cerrado (Cavalcanti et al 2015), as well as recently described species such as P. longipes and M. spinosispora, which are only registered in ground and aerial litter (Walker et al 2014;Treviño-Zevallos & Lado 2020). The type material of D. verrucisporum was collected on dead leaves in the Panama Canal Zone, as well as in other countries such as Mexico (López & García 1996), confirming the species preference for ground litter.…”
Section: Discussionsupporting
confidence: 62%
“…Among the species identified in the present study, A. cinerea, P. cinereum, P. viride and S. fusca are common in ground litter and other microhabitats (Bezerra et al 2014). Some of the species obtained in this study are typically found in the ground litter, such as C. leucocephalum and L. scintillans, which have records as foliicolous in Atlantic Rainforest and Cerrado (Cavalcanti et al 2015), as well as recently described species such as P. longipes and M. spinosispora, which are only registered in ground and aerial litter (Walker et al 2014;Treviño-Zevallos & Lado 2020). The type material of D. verrucisporum was collected on dead leaves in the Panama Canal Zone, as well as in other countries such as Mexico (López & García 1996), confirming the species preference for ground litter.…”
Section: Discussionsupporting
confidence: 62%
“…El primer registro de un Myxomycete en Perú data de 1829 (Rudolphi, 1829), pero hay que esperar hasta el siglo XXI para disponer de los primeros listados provisionales de las especies que habitan en el paıś Rojas et al, 2011). En los últimos 10 años, sin embargo, el paıś ha suscitado el intereś de los investigadores y, entre los años 2012 y 2018, el proyecto Myxotropic (www.myxotropic.org), ha realizado estudios de extensos territorios y múltiples ecosistemas (Lado et al, 2016(Lado et al, , 2019Treviño-Zevallos & Lado, 2020b;Treviño-Zevallos, 2021;Treviño-Zevallos et al, 2023), lo que ha permitido descubrir nuevas especies (Wrigley de Basanta et al, 2015Basanta et al, , 2018 y poseer un conocimiento mayor y más preciso sobre la mixobiota peruana. En la actualidad, Perú cuenta con 230 especies de Myxomycetes catalogadas, lo que le sitúa entre los paıśes con más diversidad y riqueza de especies de Sudamérica y el Neotrópico (Treviño-Zevallos et al, 2023).…”
Section: Introduccionunclassified